Urgensi Pelatihan Manajemen Ikhlas: Studi Hadis - Yunita Mardila; Busro; Asep Saeful Mimbar (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about sincerity. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about sincerity in the history of Ahmad No. 419. The results and discussion of this study indicate that the status of the hadith has the quality of hasan li ghairihi with the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 419 it is relevant to use the spirit of sincere implementation to the need for sincere management training by Islamic institutions so that sincerity can be carried out effectively and consistently.